(untitled) (Research, Society and Development, 2021)
The Federal Institute of Education, Science and Technology of Mato Grosso - IFMT is a centenary institution, with a staff of an average of 1,900 employees, with its vision of integral human education, training people for life and for the world of work, with a rich process of continuing education and/or development of people throughout their career. There is difficulty for servers to understand the process of people development, to corroborate this understanding, the article analyzes and identifies the laws and regulations that regulate this process. The general objective of the article was to analyze the legislation, norms and guidelines that guide the process of people development at the IFMT, corroborating the understanding of the IFMT community on the subject. For this, some actions were necessary, such as: surveying and analyzing the theoretical framework on the theme of people development; identifying the laws, regulations and norms that guide the process of training employees, explaining the National Policies for the Development of People, norms and internal regulations of the IFMT. As a methodology, it began with a bibliographical and documentary review on the subject, thus being a qualitative research with an exploratory objective, of an applied nature, using the case study as a method, in which data analysis was perfno ormed, describing the process of development of people within the institution.